Perancangan Instalasi Pemanen Air Hujan - Bambang Riyanta; Sunardi Sunardi; Thoharudin Thoharudin; Fitroh Anugrah Kusuma Yudha (Medan Resource Center, 2022)
Due to the dry season in recent years longer than the dry season in previous years and the increase in population and the need for clean water use, especially in the Special Region of Yogyakarta, there has been a decrease in groundwater levels which has resulted in residents having difficulty getting groundwater. On the other hand, people do not have a culture of using rainwater to meet their daily water needs. This community service program is carried out in order to help the movement to harvest rainwater, especially in the RT 02 RW 01 area of Patangpuluhan Village, Wirobrajan District. The program is carried out by harvesting rainwater to be injected into existing wells, harvesting rainwater to be stored in reservoirs and harvesting rainwater to be injected in existing infiltration wells. The output of this community service program is in the form of an integrated system of gutters for water catchers, filters and pipelines for injection into wells, an integrated system of gutters for water catchers, filters and direct pipelines to water reservoirs and an integrated system of gutters, filters and injection pipelines into existing infiltration wells.